Răspuns :
Răspuns:
Explicație pas cu pas:
a)3[tex]\sqrt{5}[/tex] < 5[tex]\sqrt{2}[/tex]
3[tex]\sqrt{5}[/tex]=[tex]\sqrt{3^{2} *5}[/tex]=[tex]\sqrt{9*5} =\sqrt{40}[/tex] < [tex]5\sqrt{2}=\sqrt{5^{2}*2 }=\sqrt{25*2}=\sqrt{50}[/tex]
b)[tex]-6\sqrt{3} > -4\sqrt{7} \\-6\sqrt{3}=-\sqrt{6^{2}*3 }=-\sqrt{36*2}=-\sqrt{72}\\-4\sqrt{7}=-\sqrt{4^{2}*7 }=-\sqrt{16*7}=-\sqrt{112}[/tex]
c)[tex]5\sqrt{3} < 7\sqrt{2}\\5\sqrt{3}=\sqrt{5^{2}*3 }=\sqrt{25*3}=\sqrt{75}\\7\sqrt{2}=\sqrt{7^{2}*2 }=\sqrt{49*2}=\sqrt{98}[/tex]
d)[tex]2\sqrt{3} < 7\sqrt{2}\\2\sqrt{3}=\sqrt{2^{2}*3 }=\sqrt{4*3}=\sqrt{12}\\7\sqrt{2}=\sqrt{7^{2}*2 }=\sqrt{49*2}=\sqrt{98}[/tex]
e)[tex]2\sqrt{3} <3\sqrt{2} \\2\sqrt{3}=\sqrt{2^{2}*3} =\sqrt{4*3}=\sqrt{12}\\3\sqrt{2}=\sqrt{3^{2}*2 }=\sqrt{9*2}=\sqrt{18}[/tex]
f)[tex]2\sqrt{3}-3\sqrt{2} < 0\\\sqrt{12}-\sqrt{18}=-\sqrt{6}[/tex]
g)[tex]0 <2\sqrt{5}-4\\2\sqrt{5}-\sqrt{16}=\sqrt{2^{2}*5 } -\sqrt{16}=\sqrt{20}- \sqrt{16}=\sqrt{4}=2[/tex]
h)[tex]5\sqrt{2}-7 >0\\5\sqrt{2}-\sqrt{49}=\sqrt{5^{2}*2}-\sqrt{49}=\sqrt{50}-\sqrt{49}=\sqrt{1}=1[/tex]
i)[tex]-3\sqrt{3}+5 > -5\\-3\sqrt{3}+\sqrt{25}=-\sqrt{3^{2}*3}-\sqrt{25}=\sqrt{27}+\sqrt{25}= \sqrt{2}[/tex]
Sper că te-am ajutat și te rog să-mi dai coroana că am muncit mult.